2016
DOI: 10.1177/2325967116631949
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Injuries in National Football League Athletes From 2010 to 2013

Abstract: Background:There is a high incidence of anterior cruciate ligament (ACL) injuries among National Football League (NFL) athletes; however, the incidence of reinjury in this population is unknown.Purpose:This retrospective epidemiological study analyzed all publicly disclosed ACL tears occurring in NFL players between 2010 and 2013 to characterize injury trends and determine the incidence of reinjury.Study Design:Descriptive epidemiological study.Methods:A comprehensive online search identified any NFL player wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 13 publications
2
103
1
Order By: Relevance
“…For example, in the National Football League, receivers and backs have a significantly greater injury risk than players in other positions. 28 To the authors' knowledge, the highest rates of graft rupture in professional athletes are reported in female patients participating in handball (19.3%) 28 and alpine skiing (27% revision rate). 29 In the current study, there were no graft ruptures in the skiers or handball athletes, but the overall numbers of patients in these categories were too small to gain a reliable estimate of the graft rupture rate.…”
Section: Discussionmentioning
confidence: 91%
“…For example, in the National Football League, receivers and backs have a significantly greater injury risk than players in other positions. 28 To the authors' knowledge, the highest rates of graft rupture in professional athletes are reported in female patients participating in handball (19.3%) 28 and alpine skiing (27% revision rate). 29 In the current study, there were no graft ruptures in the skiers or handball athletes, but the overall numbers of patients in these categories were too small to gain a reliable estimate of the graft rupture rate.…”
Section: Discussionmentioning
confidence: 91%
“…Rates of injury and RTP have also been shown to differ by position. Dodson et al 14 discovered that certain skilled players, such as wide receivers and running backs, faced a significantly greater risk of ACL injuries than the rest of the NFL. Positional differences in the rates of RTP remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing a previously established database of publicly available information regarding ACL tears among NFL players, 14 we identified NFL players with publicly disclosed ACL tears occurring between the start of the 2010 season and the end of the 2013 season. To develop this database, an anonymized list of ACL injuries from the NFL Injury Surveillance System for the 2004 to 2013 NFL seasons was provided by Edgeworth Economics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rupture or injury to the ACL is one of the most common lower limb injuries seen in sports, with potential career ending outcomes as some athletes may fail to achieve preinjury level of performance. 24 Reinjury and graft rupture have been reported as a result of returning to play too early resulting in excessive load on a poorly rehabilitated knee. 25 Therefore, it is highly important to continuously monitor the athlete rehabilitation to ensure optimum loading of injured and recovering tissues through an individualized approach according to the sport and its physical demand.…”
Section: Stages Of Sports Injury Rehabilitation: Evidence-based Practmentioning
confidence: 99%